Wavelet‐Based River Segmentation Using Hydraulic Control‐Preserving Water Surface Elevation Profile Properties. Issue 12 (19th June 2019) - Samine Montazem, A.; Garambois, P‐A.; Calmant, S.; Finaud‐Guyot, P.; Monnier, J.; Medeiros Moreira, D.; Minear, J. T.; Biancamaria, S.
Abstract: River flow models that consider satellite observations of the water surface elevation (WSE) require meaningful segmentation into reaches. Segmentation methods involve a trade‐off between the spatial sampling and error characteristics of satellite observations, both of which impact the flow model realism/accuracy. This paper investigates the spatial properties of WSE profiles (slope and concavity) and their link with hydraulic controls (HCs) and leverages this knowledge to advance river segmentation. Fine‐scale synthetic cases were analyzed to characterize HC effects on the remotely observable WSE properties. Following this, a wavelet‐based segmentation method was developed and subsequently tested on real rivers, including test cases with measurements characteristic of the Surface Water and Ocean Topography satellite mission. The results show that the local extrema of water surface (WS) concavity are good candidates for defining reach bounds while consistently preserving the HC signatures and local flow nonuniformities (deviations from equilibrium) from fine to large spatial scales. Key Points: The hydraulic visibility of river surface profile variabilities from space is investigated Hydraulic control signatures are depicted in local extrema of water surface curvature A wavelet‐based river segmentation preserving hydraulic controls is proposed